Metal-free access to β-carbolines via single-electron transfer catalyzed by a triaryl carbenium ion pair - Zhang, Zhenguo (2023)
The β-carboline moiety exists in a wide range of drugs and natural products, but synthesis often relies on noble metals and stochiometric oxidants. Here, we develop a metal-free strategy using a triaryl carbenium ion pair as a catalyst to access β-carbolines from tryptamines and aromatic aldehydes. This protocol exhibits excellent functional group tolerance, and its practicality is demonstrated with the preparation of Eudistomin U and fluorescent compounds on gram scales. Mechanistic studies reveal that the trityl radical is generated via a single-electron transfer process and subsequently trapped by an oxygen molecule. In addition, the in-situ-generated reactive oxygen-centered radical is also found to be essential for the efficient dehydroaromatization process to afford the desired products.